HISTORY OF TEACHING ENGLISH AS A FOREIGN LANGUAGE IN INDONESIA - Florentina Suharjati (Deiksis, 2010)
This is a brief history of the development of teaching English as a foreign language in Indonesia. It covers the period from the Dutch rule up to the present. During the Dutch time,TEFL was relatively speaking successful, during the Japanese period,Dutch and English were banned, and in early independence period, there were quite a few problems relating to the materials as well as teachers. Technically the situation began to improve with the improvement of the country as a whole; however, there remains a number of persistent problems beyond the teacher’s capacity to solve. TEFL and the development of English in Indonesia continue to conduct research.Keywords: History, The Materials And Teacher, Rule